Optimisation of mixed drink made from red cabbage (Brassica oleracea L.) and roselle (Hibiscus sabdariffa L.) extracts - Nur Farah Hani M.,; Huda-Faujan N.,; Hafiza Y.,; Faridah H.,; Arifin N., (Penerbit Universiti Kebangsaan Malaysia, 2020)
Response surface methodology (RSM) was employed for optimising the formulation and processing parameters of red cabbage-roselle mixed drink. In this study, four independent variables namely red cabbage-roselle extracts concentration (30 to 70%), stingless honey concentration (1–10%), pasteurisation temperature (70–90°C), and pasteurisation time (30–300 s) were studied in order to determine the effect of the formulation (ingredients) and processing parameters towards the colour and anthocyanins content of the mixed drinks. Thirty different experimental combinations generated by RSM design were studied on the responses i.e. colour values (L*, a*, b*) and total anthocyanin content of red cabbage-roselle mixed drink. The optimal formulation and processing condition were obtained with a 70% combination of red cabbage-roselle extracts concentration and 1% of stingless honey concentration, with pasteurisation temperature, and time of 70.01°C and 284.07 s, respectively. In order to verify the models, the experimental values were compared with the predicted values to check the adequacy of the models. The experimental values were found to be in agreement with those predicted, thus, indicating the suitability of the models used by RSM to optimise the formulation and processing parameters of mixed drinks made from red cabbage and roselle extracts.